PEMBERITAAN COVID 19 DI TELEVISI DAN PENGARUHNYA TERHADAP PERILAKU MASYARAKAT DALAM MEMATUHI PROTOKOL KESEHATAN DI KABUPATEN GOWA - Irwan Misbach; Rahmawati (Fakultas Dakwah dan Komunikasi, 2022)
This study aims to determine the influence of the frequency, duration, and attention of covid-19 news on television on the behavior of the community in complying with health protocols in the Gowa Regency. Quantitative descriptive research using survey methods. The study sample was 54 respondents. Data collection using questionnaires. The analytical techniques used are multiple linear regression analysis, correlation test, t-test, F test, and determinant coefficient tests. The results showed that partially the frequency of covid-19 news on television did not affect people's behavior in complying with health protocols because respondents, most of whom worked as housewives, preferred to watch entertainment channels such as soap operas. Similarly, the duration of covid-19 news on television also partially does not affect people's behavior in complying with health protocols because people do not watch covid-19 news on television for more than 30 minutes a day. Meanwhile, the attention to covid-19 news on television partially affects people's behavior in complying with health protocols because the public has concerned, interests, and interests in covid-19 news.